Josephine Donovan. Feminist Theory: The Intellectual Traditions. Fourth edition. New York: Continuum, 2012. xvi + 287 pp. - Alexandra K Wettlaufer (Studies in 20th & 21st Century Literature, 2014)
Review of Josephine Donovan. Feminist Theory: The Intellectual Traditions. Fourth edition. New York: Continuum, 2012. xvi + 287 pp.
Keywords: feminist theory